Peculiarities of properties of the pulse plasma jet - Podzirey, Yu.S.; Porytskyy, P.V. (Вопросы атомной науки и техники, 2016)
On the basis of the detonation of the fuel cycle it is considered the possibility of a flat pulsed plasma jet designed to feed into the optical resonator of the TEA laser to the heat pump. There is a schematic diagram of a device for the production of a flat plasma jet. It is shown that the using of detonation fuel cycle leads to greater population inversion of the upper levels. Because of that the possibility is achieved to perform the TEA laser, combining both the high average and peak power. На основе детонационного топливного цикла рассмотрена возможность получения плоской пульсирующей плазменной струи, предназначенной для подачи в оптический резонатор газодинамического лазера (ГДЛ) с тепловой накачкой. Представлена принципиальная схема устройства для получения плоской плазменной струи. Показано, что использование детонационного топливного цикла приводит к большей инверсионной заселённости верхних уровней, что позволяет выполнить ГДЛ, совмещающий высокую среднюю и пиковую мощности. На основі детонаційного паливного циклу розглянута можливість одержання плаского пульсуючого плазмового струменя, призначеного для постачання до оптичного резонатору газодинамічного лазера (ГДЛ) з тепловою накачкою. Представлена принципова схема пристрою для отримання плаского плазмового струменя. Показано, що використання детонаційного паливного циклу призводить до більшої інверсної заселеності верхніх рівнів, що дозволяє виконати ГДЛ, який містить високу середню та пікову потужності.